(untitled) (Revista Inclusiones, 2020)
Nowadays, it is possible to set target guidelines for education in Russia. The amendments to the Constitution of the Russian Federation adopted in 2020 and the additions to the Law of the Russian Federation "On Education" have created a methodological basis for a broad discussion of a new educational paradigm. The Constitution of Russia and the Law of the Russian Federation "On Education" set a number of new imperatives based on traditional Russian values, which constitute amentalvalue core of the Russian civilization. The article substantiates the need for the transition of Russian education from the previousWest oriented model of modernization, which wasset by the Bologna process, to a new paradigm of education based on the values of the Russian civilization. To overcome the permanent crisis in modernizing Russian education, it is necessary to use the sociocultural phenomena of the millennial Russian civilization, to create on this basis pedagogical concepts, which would allow achieving a particular optimum of combining national educational traditions and innovations that have been brought forth byinformation technologies.